Acoustic emission during tensile deformation of copper single crystals and dislocation annihilation processes - A. PAWEŁEK; W. STRYJEWSKI; H. DYBIEC; W. BOCHNIAK (Archives of Acoustics, 2014)
The behaviour of acoustic emission (AE) during the two first stages of the tensile deformation of copper single crystals is investigated using the broad-band piezoelectric transducer for the measurement of AE energy rate ΔE/Δt, AE event rate ΔN/Δt (event density) and energy per one AE event ΔE/ΔN. The existence of some essential correlation between the AE intensity (proportional to ΔE/Δt or ΔN/Δt patterns) and the plastic flow features has been stated. Two large maxima of AE intensity have been observed: the one correlated with the onset of easy glide region and the other one with the onset of stage II of the deformation. Moreover, the mean level of the AE intensity is high in the whole easy glide region and considerably greater than the mean one at the advanced stage II of the deformation, whereas the high mean level is the smaller the smaller is the length of the easy glide region. It has been shown that the observed correlations can be qualitatively quite well explained in terms of the dislocation annihilation component of the transition acoustic radiation.